MEMUPUK PRODUKTIFITAS KERJA KOMUNITAS DIFABEL DI YOGYAKARTA INDONESIA - Alan Sigit Fibrianto; Ananda Dwitha Yuniar (Jurnal Analisa Sosiologi, 2019)
Work is the most important aspect for persons with disabilities. In this highly competitive era, people with disability in Yogyakarta are trying to break the stigma attached to them. Negative stigma that says they are not able (dis- ability or inability/ disable) from now on must be changed to different abilities (diff- ability/ difable). The purpose of this study was to determine the work productivity of people with difability in Yogyakarta who move through the limitations of limitations by opening a taxi bike (ojek) service business and city tour around the Yogyakarta City. This study uses a qualitative method with the Participatory Action Research (PAR) approach by emphasizing the empowerment patterns carried out in the people with difability community in Yogyakarta. Data obtained by observation and in-depth interviews, this was done in the physical difability community in Yogyakarta which is engaged in empowering the people with difability as a taxi bike service provider. The results showed that there are several things that underlie the formation of transportation for people with difability taxi bike which are accommodated in the physical difability community in Yogyakarta, consists of, covering aspects of democracy, equality, freedom, and welfare. Physical difability community who are active in the field of transportation services for people with difability taxi bike have become a creative, competitive, and empowering service business for people with difabilities in Yogyakarta Indonesia, which operates independently and is recognized by the public. Keywords:    community, taxi bike (ojek) of people with difability, physical difability, Participatory Action Research (PAR) AbstrakPekerjaan menjadi aspek terpenting bagi para penyandang disabilitas. Di era yang sangat kompetitif ini, difabel di Yogyakarta berupaya untuk mendobrak stigma yang melekat pada mereka. Stigma negatif yang menyebut mereka tidak mampu (dis- ability/ atau ketidak mampuan) mulai sekarang harus dirubah menjadi berbeda kemampuan (different ability/ perbedaan kemampuan). Tujuan penelitian ini adalah untuk mengetahui produktifitas kerja komunitas difabel tuna daksa di Yogyakarta yang bergerak menembus batas keterbatasan dengan membuka usaha jasa ojek dan city tour keliling kota. Penelitian ini menggunakan metode kualitatif dengan pendekatan Participatory Action Research (PAR) dengan menekankan pada pola-pola pemberdayaan yang dilakukan di dalam komunitas difabel di Yogyakarta. Data diperoleh dengan observasi dan wawancara mendalam, ini dilakukan di komunitas difabel tuna daksa di Yogyakarta yang bergerak dalam memberdayakan para difabel sebagai penyedia jasa transportasi ojek. Hasil penelitian menunjukkan bahwa ada beberapa hal yang mendasari terbentuknya transportasi ojek difabel yang diwadahi dalam komunitas difabel tuna daksa di Yogyakarta yaitu, meliputi aspek demokrasi, kesetaraan, kebebasan, dan kesejahteraan. Komunitas difabel tuna daksa yang bergerak di bidang jasa transportasi ojek difabel ini menjadi sebuah usaha jasa kreatif, kompetitif, serta pemberdayaan bagi masyarakat difabilitas di Yogyakarta Indonesia, yang bergerak secara independen dan diakui masyarakat. Kata kunci:    komunitas, ojek difabel, tuna daksa, Participatory Action Research (PAR)